Case report: Myocardial noncompaction causing massive cerebral infarction in 1 patient with eyelid edema as an early manifestation and literature review - Ge, Pingping; Zhu, Yafei (Frontiers in Pediatrics, 2023)
Objective To summarize and analyze the early clinical manifestations, risk factors, treatment and prognosis of myocardial noncompaction in children, and to provide scientific basis for early and effective intervention. Methods Combined with a case of myocardial noncompaction with massive cerebral infarction in a child, the related research reports of myocardial noncompaction in children were analyzed retrospectively. Results Myocardial noncompaction in children is cardiomyopathy caused by abnormal myocardial compaction during embryonic development. Feeding intolerance, dyspnea, chest tightness, fatigue, eyelid edema and other non-specific manifestations may occur in the early stage. It is easy to miss the diagnosis and misdiagnosis in clinical diagnosis and treatment, leading to intractable heart failure, nausea and arrhythmia, thromboembolism and even sudden death and other serious complications. Early diagnosis, symptomatic treatment, control of complications and regular follow-up can prevent the occurrence of serious complications and reduce mortality. Conclusion: There is no specific clinical manifestation in the early stage of myocardial noncompaction in children. If it is not detected early and treated symptomatically, the prognosis is poor and the mortality is high. Therefore, clinicians should fully improve the understanding of the early clinical manifestations of this disease, give early diagnosis and early intervention to children, reduce the occurrence of serious complications and improve the survival rate.